Inventarisasi Jenis Talas-Talasan (Araceae) di Tepian Sungai Lembah Gunung Mandiangin KHDTK Universitas Lambung Mangkurat - Muhammad Maulana; Bunda Halang; Mahrudin Mahrudin (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
Information on plant species in special forest areas is important to support the conservation and management of biological resources, so that plant inventory needs to be carried out to determine their existence and characteristics. This study was conducted with the aim of describing the taro (Araceae) species found on the banks of the Mandiangin Mountain Valley River, KHDTK, Lambung Mangkurat University. Sampling of taro (Araceae) plants was carried out through the exploration method, namely by exploring the path around the banks of the Mandiangin Mountain Valley River. The results of the study found 18 types of taro (Araceae) which are classified into several genera, including Caladium bicolor, Caladium bicolor (Aiton) Vent, Caladium bicolor var. florida, Aglaonema commutatum, Aglaonema sp., Syngonium podophyllum, Syngonium angustatum, Colocasia esculenta (L.), Colocasia sp., Philodendron erubescens, Philodendron bipinnatifidum, Xanthosoma sagittifolium, Amydrium medium, Alocasia macrorrhiza, Dieffenbachia sp., Amorphophallus sp., Homalomena sp., and Monstera deliciosa. The diversity of these species indicates that the humid, shady, and organic-rich riverbank environment is a suitable habitat for the growth of taro (Araceae) species. Environmental factors such as soil pH, soil moisture, temperature, altitude, and light intensity also support the existence and distribution of taro (Araceae) plants in this area. The results of this study are expected to be basic data on biodiversity, a reference for identifying local taro (Araceae), and supporting materials for learning and management of the KHDTK area of ​​Lambung Mangkurat University.